1999
DOI: 10.1016/s0896-6273(00)80827-2
|View full text |Cite
|
Sign up to set email alerts
|

BMPs as Mediators of Roof Plate Repulsion of Commissural Neurons

Abstract: During spinal cord development, commissural (C) neurons, located near the dorsal midline, send axons ventrally and across the floor plate (FP). The trajectory of these axons toward the FP is guided in part by netrins. The mechanisms that guide the early phase of C axon extension, however, have not been resolved. We show that the roof plate (RP) expresses a diffusible activity that repels C axons and orients their growth within the dorsal spinal cord. Bone morphogenetic proteins (BMPs) appear to act as RP-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
230
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(236 citation statements)
references
References 89 publications
6
230
0
Order By: Relevance
“…Additionally, roof plate explants derived from mice lacking BMP7 show a markedly decreased ability to deflect axons in vitro. A rapid and direct effect on commissural axon growth was demonstrated by the ability of BMP7 to promote the collapse of cultured commissural growth cones (Augsburger et al, 1999). Consistent with an in vivo role for BMP7, commissural axon pathfinding defects have apparently been observed in the spinal cords of BMP7 knockout mice (see Augsburger et al, 1999).…”
Section: Vertebrate Spinal Cord: Bone Morphogenetic Proteinsmentioning
confidence: 89%
See 4 more Smart Citations
“…Additionally, roof plate explants derived from mice lacking BMP7 show a markedly decreased ability to deflect axons in vitro. A rapid and direct effect on commissural axon growth was demonstrated by the ability of BMP7 to promote the collapse of cultured commissural growth cones (Augsburger et al, 1999). Consistent with an in vivo role for BMP7, commissural axon pathfinding defects have apparently been observed in the spinal cords of BMP7 knockout mice (see Augsburger et al, 1999).…”
Section: Vertebrate Spinal Cord: Bone Morphogenetic Proteinsmentioning
confidence: 89%
“…The roof plateenriched expression of several chondroitin (Snow et al, 1991;Katoh-Semba et al, 1995;Engel et al, 1996;Katoh-Semba et al, 1998) and keratan (Cole and McCabe, 1991; sulfate proteoglycans which are capable of inhibiting neurite outgrowth in vitro, provides support for this hypothesis. More recently, it was demonstrated that the roof plate is capable of deflecting and reorienting Netrin-1-responsive commissural axons from E11 rat dorsal spinal cord explants (Augsburger et al, 1999). The ability of roof plate explants to deflect commissural axons from as far away as 100 m suggested that this repulsive activity was associated with a diffusible molecule secreted by roof plate cells.…”
Section: Vertebrate Spinal Cord: Bone Morphogenetic Proteinsmentioning
confidence: 99%
See 3 more Smart Citations